2012
DOI: 10.1215/03616878-1538629
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Law in Public Health Preparedness: Opportunities and Challenges

Abstract: We report the results of a study designed to assess and evaluate how the law shapes the public health system's preparedness activities. Based on 144 qualitative interviews conducted in nine states, we used a model that compared the objective legal environment with how practitioners perceived the laws. Most local public health and emergency management professionals relied on what they perceived the legal environment to be rather than on an adequate understanding of the objective legal requirements. Major reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…management workforces, Jacobson and colleagues found that knowledge and perception of emergency preparedness laws varied greatly, with ''a clear disconnect'' between the actual legal environment (ie, codified law and accompanying regulations) and individuals' perceptions or interpretations of the law. 26 This raises several implications for the study: (1) EMS workers may have been unaware of the presence of the emergency laws considered in this analysis;…”
Section: Discussionmentioning
confidence: 99%
“…management workforces, Jacobson and colleagues found that knowledge and perception of emergency preparedness laws varied greatly, with ''a clear disconnect'' between the actual legal environment (ie, codified law and accompanying regulations) and individuals' perceptions or interpretations of the law. 26 This raises several implications for the study: (1) EMS workers may have been unaware of the presence of the emergency laws considered in this analysis;…”
Section: Discussionmentioning
confidence: 99%
“…8 The research to date on willingness to respond strongly suggests the need for greater understanding by health department leaders and line staff of the ethical and attendant legal dimensions of infectious disease response in advance of an outbreak. 9,10 The decision of local health department employees to respond to an infectious disease crisis can become a balance of personal (eg, family wellbeing) and professional (eg, welfare of the community served by the health department during the event) responsibilities. A tension thus emerges between their rights as individuals and their commitment to the public good.…”
mentioning
confidence: 99%
“…7 In addition, equal protection claims may arise from individuals who believe they received inferior services because of their race, ethnicity, or socioeconomic class. 29,48 Failure to Prepare Health care entities have an obligation to prepare for emergencies, and lawsuits against hospitals and other health care entities alleging liability for patient harms are brought and settled routinely in the United States. 30,56,57 When patient harms can be linked to an entity's failure to prepare sufficiently for emergencies, defending the claims can be difficult because emergency preparedness is mandated by law, endorsed by practice, and ultimately beneficial to * This is to be distinguished from careful, sensitive, and deliberative decisions regarding do-not-resuscitate status or foregoing nonbeneficial treatment in a patient who is terminally ill.…”
Section: Other Potential Claims Constitutional Violationsmentioning
confidence: 99%
“…Evidence reveals that concern or confusion about various legal protections during public health emergencies may interfere with providers' responsiveness and willingness to volunteer. 2,7,11,26,[29][30][31][32][33][34][35] Ethically, providing necessary medical care should not be hampered by legal considerations.…”
Section: Introductionmentioning
confidence: 99%